Extracellular vesicle microRNA cargoes: candidates for diagnosis and targeted therapy of cutaneous wound healing - Mai Thi Le; Huy Hoang Dao; Xuan-Hung Nguyen; Tinh Van Nguyen; Tu Dac Nguyen; Uyen Thi Trang Than (Annals of Medicine)
Background Non-healing wounds lead to tissue dysfunction, contributing to pathological conditions and compromising overall health. Recently, microRNAs have been shown to regulate diverse biological events, including cell migration, proliferation, angiogenesis, scar formation, and wound closure. Interestingly, cells selectively sort microRNAs into extracellular vesicles, which can be up-taken by cells to regulate the healing process. Consequently, extracellular vesicles and their microRNA content serve as an in-situ reservoir, providing tissue-specific signals on demand.Aims and methods This review aims to explore the association between microRNAs and the wound healing process, and the roles of extracellular vesicle-derived miRNAs in different cell populations within the wound microenvironment. We searched PubMed, Web of Science, and Scopus using the keywords: exosomes, mesenchymal stem cell-derived exosomes, wound healing, and microRNA. Relevant data were collected and summarized.Results This review provided information about extracellular vesicles, microRNA biogenesis, and their roles in wound healing. Results highlighted the roles of extracellular vesicle-derived microRNAs in anti-inflammatory responses, promoting cell migration, proliferation, and differentiation while inhibiting apoptosis during wound repair. Beyond their natural functions, extracellular vesicles and their microRNA cargoes hold significant potential for therapeutic and diagnostic applications in wound healing. We also outlined the potential use of extracellular vesicle-derived microRNAs as drug delivery systems and miRNA-based monitoring tools.Conclusion Extracellular vesicle-derived microRNAs play important roles in wound healing. Despite their promise, challenges such as lack of standardization in isolation, precise delivery, and reliable quantification methods remain obstacles for clinical implementation in disease diagnosis and prognosis.